1994
DOI: 10.1055/s-2008-1066132
|View full text |Cite
|
Sign up to set email alerts
|

Peptidergic Nerves in Hirschsprung's Disease and Its Allied Disorders*

Abstract: To clarify the significance of peptidergic nerves in Hirschsprung's disease (aganglionosis), hypoganglionosis, and neuronal intestinal dysplasia (NID), we investigated enteric nerve responses in colonic tissues obtained from patients with these diseases. Colonic tissue specimens were obtained from 12 patients with aganglionosis, 8 patients with hypoganglionosis, and 6 patients with NID. Colon specimens from 20 patients without constipation were used as controls. A mechanograph was used to evaluate in vitro col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 5 publications
0
17
0
1
Order By: Relevance
“…They also observed the absence of nitric oxide as a neurotransmitter in the muscle and concluded that this was most likely to be responsible for the spasticity of the aganglionic segment [15]. Studies on the peptidergic innervation of the aganglionic intestinal segment in Hirschsprung's disease patients have also demonstrated a marked reduction in the density of nerve fibres storing vasoactive intestinal peptide (VIP), substance P (SP), enkephalin, and gastrin releasing peptide (GRP) [11,16].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…They also observed the absence of nitric oxide as a neurotransmitter in the muscle and concluded that this was most likely to be responsible for the spasticity of the aganglionic segment [15]. Studies on the peptidergic innervation of the aganglionic intestinal segment in Hirschsprung's disease patients have also demonstrated a marked reduction in the density of nerve fibres storing vasoactive intestinal peptide (VIP), substance P (SP), enkephalin, and gastrin releasing peptide (GRP) [11,16].…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports have documented the absence of inhibitory enteric neurons and ganglia in the aganglionic segment as a possible cause of pronounced colonic spasticity seen in patients with Hirschsprung's disease [8][9][10][11]. Several investigators have studied nitrergic innervation and nitric oxide (NO) activity in the ganglionic and aganglionic bowel [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…No specific organic cause can be found in approximately 90% of the children, and a diagnosis of Functional or Idiopathic chronic constipation is made in these children. Even within a group of children with refractory chronic constipation, in eighty percent no known abnormality was found in their rectal suction biopsy [118]. It is estimated that 5% of all children suffer from chronic constipation lasting more than six months.…”
Section: Motility Disorders and Ensmentioning
confidence: 98%
“…Histochemistry for acetylcholinesterase (AChE), the enzyme that breaks down ACh into choline and acetic acid, is used to identify cholinergic nerves but is not a selective marker for cholinergic neurons. AChE immunoreactivity (AChE-IR) is routinely used to demonstrate enlarged nerve trunks in the diagnosis of Hirschsprung's disease (Johnson et al 1995;Tomita et al 2004).…”
mentioning
confidence: 99%